2022
DOI: 10.1103/physrevb.105.195140
|View full text |Cite
|
Sign up to set email alerts
|

Variational methods for contracting projected entangled-pair states

Abstract: The norms or expectation values of infinite projected entangled-pair states (PEPS) cannot be computed exactly, and approximation algorithms have to be applied. In the last years, many efficient algorithms have been devised-the corner transfer matrix renormalization group (CTMRG) and variational uniform matrix product state (VUMPS) algorithm are the most common-but it remains unclear whether they always lead to the same results. In this paper, we identify a subclass of PEPS for which we can reformulate the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Evaluating general spin-spin correlation functions can in principle be done with tensor networks (see e.g. [82][83][84]): the complexity is similar to computing dynamical correlation functions for one-dimensional quantum systems in imaginary time 8 . The construction based on tiles, however, requires a specific implementation that is left for future investigation.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…Evaluating general spin-spin correlation functions can in principle be done with tensor networks (see e.g. [82][83][84]): the complexity is similar to computing dynamical correlation functions for one-dimensional quantum systems in imaginary time 8 . The construction based on tiles, however, requires a specific implementation that is left for future investigation.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…which we evaluate using the methods from Ref. [38]. We plot this quantity through a path of the Brillouin zone for different PEPS bond dimensions, showing a smooth behavior at the X point and a vanishing value at the Γ point-exactly what one would expect for a gapped spin liquid (long-range order would manifest itself as a divergence at the X point).…”
mentioning
confidence: 87%
“…This class of tensor-network states can be formulated [34] and variationally optimized [35,36] directly in the thermodynamic limit. The control parameters are the bond dimension D, controlling the amount of entanglement in the PEPS wave function, and the environment bond dimension χ, which is introduced when contracting the PEPS approximately with boundary MPS [28,37,38] or the corner-transfer matrix renormalization group (CTMRG) [39][40][41][42][43][44]. When simulating a critical model, a variational PEPS wave function typically exhibits a finite correlation length, which provides a length scale that can be used to extrapolate variational PEPS results [45][46][47][48].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, it has been shown that, for tensor networks, local optimizations generally result in better performance than global optimizations [65]. While interesting developments in the field of tensor networks are continuously appearing [66][67][68], important limitations still exist, for example for dimensions larger than one and for long range systems.…”
mentioning
confidence: 99%